2014
DOI: 10.1016/j.atherosclerosis.2014.09.022
|View full text |Cite
|
Sign up to set email alerts
|

Circulating IGFBP-2 levels are incrementally linked to correlates of the metabolic syndrome and independently associated with VLDL triglycerides

Abstract: In our cohort, IGFBP-2 levels <221.5 ng/mL are incrementally associated with a detrimental plasma lipoprotein-lipid profile. After adjustment for covariates, IGFBP-2 remained independently associated with VLDL-TG but not HDL-C levels. This study supports further investigations in other populations and validation of IGFBP-2 as a biomarker of early dyslipidemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
37
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 41 publications
(48 reference statements)
11
37
0
1
Order By: Relevance
“…They also exhibited decreased insulin sensitivity assessed according to higher fasting insulin levels and HOMA index. These findings are consistent with previous reports [11][12][13][14] and might suggest that IGFBP-2 could be used as a biomarker of metabolic alterations linked to visceral obesity. Interestingly, SV indexed to the 2.04 power of height or "ideal BSA" remained associated with IGFBP-2 levels.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…They also exhibited decreased insulin sensitivity assessed according to higher fasting insulin levels and HOMA index. These findings are consistent with previous reports [11][12][13][14] and might suggest that IGFBP-2 could be used as a biomarker of metabolic alterations linked to visceral obesity. Interestingly, SV indexed to the 2.04 power of height or "ideal BSA" remained associated with IGFBP-2 levels.…”
Section: Discussionsupporting
confidence: 93%
“…8,9 Recent experimental studies showed that overexpression of human IGFBP-2 in rodents protects against age and diet-induced insulin resistance. 10 Consistently, lower circulating levels of IGFBP-2 have been associated with obesity, insulin resistance, and dyslipidemia in humans, [11][12][13] leading to the postulate that plasma IGFBP-2 could be a biomarker for the MetS. 14 We therefore hypothesized that circulating levels of IGFBP-2 could be associated with the worsening of myocardial structure and function in AS.…”
mentioning
confidence: 96%
“…In the present study, total circulating IGFBP-2 levels were within the range reported in men with mild dyslipidemia and increased adiposity Log-transformed variables. [8,12,33,34]. Following the 1-year intervention, average IGFBP-2 levels were increased by 43%, which is consistent with the upregulation observed after weight loss achieved by dieting alone [19].…”
Section: Discussionsupporting
confidence: 78%
“…Additional transversal associations between IGFBP-2 levels and components of the lipoprotein-lipid profile, mostly TG and HDL cholesterol, were also described by others [11,13]. Further analyses suggested that subjects with low IGFBP-2 levels display an increased number of TG-rich particles as assessed by elevated apo B concentrations [12]. In turn, both overexpression of IGFBP-2 in mice and IGFBP-2 treatment to 3T3-L1 adipocyte cultures enhance uptake and metabolism of energy substrates, through yet unclear, partially IGF-1-independent mechanisms, including a possible attenuation of α5β1 integrins and intracellular PTEN signaling [14,15].…”
Section: Introductionmentioning
confidence: 52%
See 1 more Smart Citation